Comparative study between modified path matrix approach, modified gradient method and Bocher's technique to detect isomorphism in EGTs. (2021) - Mustafa, Jiyaul; Hasan, Ali
Abstract: The Structural synthesis and topological analysis of Epicyclic gear trains (EGTs) have been great research area for checking isomorphic properties of mechanisms since few decades. In this paper, comparative analysis was done between three methods as Modified path matrix approach (MPM), Modified gradient method (MGM) and Bocher's Technique (BT) for checking isomorphism in EGTs and its inversions. These methods have computed on the basis of reliability of results, computational application & structural properties for theirs merits and demerits by using MATLAB software. The methods have been compared with examples of 4-link EGTs and 6-link EGTs One-DOF. All examples have found satisfactory results on the basis of literature.